Lightning on Overhead Transmission Lines: Dangers and Safety Measures - Imo, F. U.; Nwabueze, C. A. (Darul Yasin Al Sys, 2025)
Lightning-induced disruptions on power transmission lines remain a major cause of faults in high-voltage systems, often resulting in service interruptions, equipment damage, and compromised grid stability. This study examines the primary mechanisms through which lightning impacts transmission infrastructure, including back flashover, shielding failure, and induced overvoltage. To mitigate these effects and enhance system reliability, a range of protective measures are analyzed. These include enhancing insulation levels, installing controllable discharge lightning rods, reducing tower grounding resistance, deploying coupling ground wires, and utilizing line surge arrestors. Each technique is evaluated for its effectiveness in minimizing lightning-related faults and ensuring a stable power supply. The findings emphasize the importance of integrated protection strategies tailored to specific environmental and system conditions. By implementing these safeguarding measures, utilities can significantly reduce lightning-related outages and improve the resilience of power transmission networks.